ANALISIS DETERMINAN KINERJA KEUANGAN DENGAN PERAN MODERASI DEWAN KOMISARIS INDEPENDEN : STUDI EMPIRIS PADA SEKTOR CONSUMER NON-CYCLICAL DI INDONESIA - Lisa Cahya Zaharani; Maulida Nurul Innayah; Wida Purwidianti; Alfato Yusnar Kharismasyah (LPPM STIE Muhammadiah Bandung, 2025)
This research aims to investigate how leverage, firm size, and market value impact financial performance, along with exploring the moderating role of independent commissioners in companies within the non-cyclical consumer sector listed on the Indonesia Stock Exchange. Utilizing a quantitative methodology, the study employs documentation and purposive sampling techniques. The sample comprises 41 companies, with a total of 150 observations spanning from 2020 to 2023. Data were analyzed using Stata version 17 through panel data regression models, specifically Fixed Effect and Random Effect models, chosen based on preliminary tests. The results reveal that independent commissioners positively influence financial performance. Conversely, leverage, firm size, and market value show no significant effect on financial performance. The moderation analysis further demonstrates that independent commissioners enhance the relationship between leverage and financial performance, while they do not moderate the effects of firm size and market value on financial outcomes. These findings underscore the crucial supervisory role of independent commissioners, especially in capital structure management, to improve the financial performance of firms.